The cardiovocal syndrome caused by a giant thoracic aorta aneurysm - Bouchentouf, Rachid (2020)
The ortner’s syndrome o the cardio vocal syndrome is a rare syndrome described  as  a  left  recurrent  laryngeal  paralysis  caused  by  a  specific cardiovascular pathology. The  thoracic  aortic  aneurysm  is  rarely  associated  with  cardiovocal  syndrome; it is reported with aortic arch aneurysm and with giant thoracic aneurysm. It is reported the case of a 75 year-old woman with dysphonia caused by a giant thoracic aortic aneurysm.